The economics of regulation in agriculture [ compliance with public and private standards - Brouwer, Floor; Fox, Glenn; Jongeneel, R. A. (CABI, 2012)
This work debates and investigates the cross-compliance system - whereby farmers comply with certain standards relating to the environment, food safety and animal and plant health. The book discusses cross-compliance in the context of existing standards on-farm costs and the competitiveness of farm businesses. Analysing the economics of regulation both within the internal market of the EU and the broader world market by examining a broad range of agricultural products. This resource will be of value to agriculture and resource economists, policy makers, researchers and students in environment.